Comparison of the efficacy of Trazodone hydrochloride tablets alone and in combination with press-needles in the treatment of post-stroke depression - Cui, Qiaoyi; Wei, Wei (Journal of the Pakistan Medical Association, 2023)
The purpose of this study was to compare the efficacy of Trazodone hydrochloride tablets alone and in combination with press-needles in the treatment of post-stroke depression. One hundred and four post-stroke depression patients, admitted to Yantaishan Hospital, China, from August 2019 to June 2021, were randomly divided in two groups: Group A (n=52) and Group B (n=52). Group A was given oral Trazodone hydrochloride tablets, while Group B was treated with press-needle and Trazodone hydrochloride tablets. Post treatment assessment revealed that after treatment, National Institutes of Health Stroke Scale scores, Hamilton Depression Rating Scale scores, serum 5-hydroxytryptamine and brain-derived neurotrophic factor levels of Group B were lower than those of Group A (all p<0.001). Treatment efficiency of Group B was higher than that of Group A (p=0.014). —Continue